2020
DOI: 10.1186/s41687-020-00195-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes and experiences from the perspective of colorectal cancer survivors: meta-synthesis of qualitative studies

Abstract: Background: Colorectal cancer (CRC) is prevalent in the developed world. Favourable survival rates highlight the need to better understand CRC survivors' experiences of long-term impacts of treatment, which can in turn inform decision making. This systematic review aimed to identify and synthesise CRC survivors' experiences of long-term impacts on health-related quality of life. Methods: We searched Medline, Embase and PsychINFO from inception to January 2019. Qualitative studies describing CRC survivors' expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 56 publications
(249 reference statements)
5
69
1
Order By: Relevance
“…The mean scores in the subscale “sexuality” are lower than in the other subscales, which may indicate that sexuality remains a challenge after ostomy surgery as shown in several other studies. 4 , 5 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…The mean scores in the subscale “sexuality” are lower than in the other subscales, which may indicate that sexuality remains a challenge after ostomy surgery as shown in several other studies. 4 , 5 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…This knowledge gap has implications for both clinicians, patients, and their informal caregivers. A previous review showed that many CRC survivors find ways to self-manage their symptoms through trial and error rather than seek professional help [30]. Self-help strategies are often not evidence-based, so it may not be effective and perhaps even detrimental, worsening symptoms or impairment.…”
Section: Discussionmentioning
confidence: 99%
“…To develop a set of domains and subdomain items for the a priori analytical framework, we reviewed literature on core outcome sets for PRE and PRO measures [2,23,53] and mixed-methods approaches for analyzing PRE and PRO data [12,[54][55][56][57]. Our conceptual approach to PRE and PRO domain coding is presented in Figure 3.…”
Section: Pre and Pro Domain Codingmentioning
confidence: 99%